2021
DOI: 10.2174/0929867327666200812215852
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing: A Strategy for Discovering Inhibitors against Emerging Viral Infections

Abstract: Background: Viral diseases are responsible for several deaths around the world. Over the past few years, the world has seen several outbreaks caused by viral diseases that for a long time seemed to possess no risk. These are diseases that have been forgotten for a long time and, until nowadays, there are no approved drugs or vaccines, leading the pharmaceutical industry and several research groups to run out of time in the search for new pharmacological treatments or prevention methods. In this context, drug r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 284 publications
0
12
0
Order By: Relevance
“…It involves evaluating drugs already approved by regulatory agencies such as the FDA to develop new uses, which can reduce the development time and costs associated with bringing new drugs to market. This approach offers opportunities to identify promising drug candidates that can be repurposed with the potential to improve the lives of patients [ 264–266 ]. Drug repurposing, also known as drug repositioning, is the process of discovering new therapeutic uses for existing drugs that are already approved for other indications [ 264 ].…”
Section: Drug Repurposingmentioning
confidence: 99%
“…It involves evaluating drugs already approved by regulatory agencies such as the FDA to develop new uses, which can reduce the development time and costs associated with bringing new drugs to market. This approach offers opportunities to identify promising drug candidates that can be repurposed with the potential to improve the lives of patients [ 264–266 ]. Drug repurposing, also known as drug repositioning, is the process of discovering new therapeutic uses for existing drugs that are already approved for other indications [ 264 ].…”
Section: Drug Repurposingmentioning
confidence: 99%
“…CADD has until now led to the discovery of more than 70 approved drugs [ 4 ], from Captopril in 1981 [ 150 , 151 ] to Remdesivir in 2021 [ 152 ]. Two important categories of CADD, structure-based drug design (SBDD) and ligand-based drug design (LBDD), are highlighted in this review.…”
Section: Computer-aided Drug Designmentioning
confidence: 99%
“…35 Sofosbuvir is approved for the treatment of hepatitis C. Also, the drug has excellent results against other viruses like the ZIKV. 22 Sofosbuvir especially can be useful in the early phase of COVID-19 before the virus attacks the lung cells. 23 Recent studies showed that the active form of sofosbuvir terminates RdRp activity.…”
Section: Rna Dependent Rna Polymerase (Rdrp): Sofosbuvirmentioning
confidence: 99%
“…This study indicated that simeprevir was stable in the protease binding pocket and had suitable interaction with catalytic residues Cys145 and His41. 22 According to a molecular docking study conducted by Rahman et al 6 , simeprevir was introduced as one of the best candidates against SARS-CoV-2 Mpro. Simeprevir had several bonds with amino acid residues in addition to hydrogen bonds and electrostatic interactions.…”
Section: Rna Dependent Rna Polymerase (Rdrp): Sofosbuvirmentioning
confidence: 99%